2023
DOI: 10.1093/humrep/dead028
|View full text |Cite
|
Sign up to set email alerts
|

Serum persistent organic pollutants and diminished ovarian reserve: a single-exposure and mixture exposure approach from a French case–control study

Abstract: STUDY QUESTION Are persistent organic pollutants (POPs) associated with a diminished ovarian reserve (DOR) in women of reproductive age? SUMMARY ANSWER Amongst 17 POPs detected in over 20% of serum samples, only p,p′-DDE was significantly associated with an increased risk of DOR, and β-hexachlorocyclohexane (β-HCH) was significantly associated with a decreased risk of DOR whilst mixture analyses yielded non-significant associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…A prospective cohort study including 109 women seeking fertility treatment found that urinary TCS concentrations were inversely associated with AFC, thus affecting ovarian reserve ( 136 ). A French case-control study detected 17 POPs in serum samples, with only p,p’-dichlorodiphenyldichloroethylene (DDE) being significantly associated with an increased risk of DOR ( 137 ). Another case-control study utilizing Bayesian kernel machine and logistic regressions, validated the combined and individual effects of EDCs on DOR, with a particular emphasis on the influence of benzophenone-4 (BP4) ( 138 ).…”
Section: Introductionmentioning
confidence: 99%
“…A prospective cohort study including 109 women seeking fertility treatment found that urinary TCS concentrations were inversely associated with AFC, thus affecting ovarian reserve ( 136 ). A French case-control study detected 17 POPs in serum samples, with only p,p’-dichlorodiphenyldichloroethylene (DDE) being significantly associated with an increased risk of DOR ( 137 ). Another case-control study utilizing Bayesian kernel machine and logistic regressions, validated the combined and individual effects of EDCs on DOR, with a particular emphasis on the influence of benzophenone-4 (BP4) ( 138 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to statistical data, the global success rate of live birth per IVF cycle is approximately 30% to 40% [ 10 , 11 ]. Factors such as age, body weight, ovarian reserve quantity and quality, unhealthy lifestyle choices, and exposure to environmental pollutants can all influence the likelihood of a successful outcome [ 10 , 12 , 13 ]. Among these factors, decreased ovarian reserve (DOR) presents a particularly formidable obstacle and frequently results in IVF failure [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adipose tissue is, therefore, considered the main reservoir of these compounds, accounting for all routes and sources of exposure, and represents a stable and long-term biomarker of exposure to these chemicals [15][16][17]. The relationship between POP exposure and increased risk for this estrogen-dependent disease is biologically plausible since many OCPs and PCBs have been shown to interact with estrogen and/or androgen receptors [18][19][20][21][22], and epidemiological evidence has been published for a variety of hormone-dependent diseases, e.g., breast cancer [23,24], anovulation [25], ovarian function [26,27], infertility [28], preterm birth [29], polycystic ovarian syndrome [30], fibroids [31], and endometriosis [32]. Nevertheless, while some authors pointed out that some POPs might be related to an increased risk for endometriosis [33][34][35], others have not found any association between POP exposure and endometriosis risk [36][37][38].…”
Section: Introductionmentioning
confidence: 99%